2020
DOI: 10.1177/1945892420916393
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Function Changes at High Altitude

Abstract: Background An ever-increasing number of people are involved in sport activities at high altitude. Objective This study aimed to evaluate the pulmonary and nasal functions, including nasal cytology, in healthy volunteers moving for 1 week from an altitude of 2000 m to another of 3400 m. Methods Peak nasal inspiratory flow (PNIF), pulmonary function, including peak expiratory flow (PEF), mucociliary transport time (MCTt), nasal cytology, and oxygen saturation (O2 sat) were studied in 5 different occasions—T1: at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, researchers continue to explore the relationship between physiologic and immunologic responses to variable exercise conditions and environmental exposures. One team found that increased altitude of healthy participants increased peak nasal inspiratory flow (PNIF), mucociliary transport time (MCTt) and neutrophil count, and decreased peak expiratory flow (PEF) and oxygen saturations (31). Similarly, another study observed prolonged MCTt with swimming, both effects transient and resolved to baseline following completion of swimming or descent from higher altitude (32).…”
Section: Upper Respiratory Infectionsmentioning
confidence: 99%
“…Furthermore, researchers continue to explore the relationship between physiologic and immunologic responses to variable exercise conditions and environmental exposures. One team found that increased altitude of healthy participants increased peak nasal inspiratory flow (PNIF), mucociliary transport time (MCTt) and neutrophil count, and decreased peak expiratory flow (PEF) and oxygen saturations (31). Similarly, another study observed prolonged MCTt with swimming, both effects transient and resolved to baseline following completion of swimming or descent from higher altitude (32).…”
Section: Upper Respiratory Infectionsmentioning
confidence: 99%
“…Overall, olfactory loss was noted in over 50% of asymptomatic subjects, and there was an independent association between age and smell threshold, discrimination, and identification. This issue's focus on nasal pathophysiology is rounded out by the Ottaviano et al 8 study that investigates the effect of increased altitude on nasal physiology and pulmonary physiology, in subjects who were exposed to an acute change in altitude of 1400 meters. As expected, peak nasal inspiratory flow and mucociliary transport times were noted to increase, likely due to hypoxia-induced vasoconstriction within the nose.…”
mentioning
confidence: 99%